SINTESIS NANOPARTIKEL NIKEL HIDROKSIDA SECARA ELEKTROKIMIA DENGAN PENAMBAHAN NA-SITRAT SEBAGAI AGEN PEREDUKSI - Yanantra Budi Pramana (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
Nickel hydroxide nanoparticles have been synthesized electrochemically. The synthesis based on electrolysis system which bare nickels were used for both cathode and anode. The potential applied during electrolysis was from 25 and 55 V. The sodium citrate concentration 0.3 M, was used to study optimal condition of nickel hydroxide nanoparticles formation. UV-Vis spectroscopy, X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (TEM) were used to characterize themicrostructure and morphology of the products. Spherical nanoparticles were obtained by this method. The generated particles are nearly spherical with a mean size 60 nm depending on synthesis condition. Keywords: Nickel hydroxide nanoparticles, electrochemically, high voltage